Established amyloid‐β pathology is unaffected by chronic treatment with the selective serotonin reuptake inhibitor paroxetine. Issue 1 (23rd May 2018) - Severino, Maurizio; Sivasaravanaparan, Mithula; Olesen, Louise Ø.; von Linstow, Christian U.; Metaxas, Athanasios; Bouzinova, Elena V.; Khan, Asif Manzoor; Lambertsen, Kate L.; Babcock, Alicia A.; Gramsbergen, Jan Bert; Wiborg, Ove; Finsen, Bente
Abstract: Introduction: Treatment with selective serotonin reuptake inhibitors has been suggested to mitigate amyloid‐β (Aβ) pathology in Alzheimer's disease, in addition to an antidepressant mechanism of action. Methods: We investigated whether chronic treatment with paroxetine, a selective serotonin reuptake inhibitor, mitigates Aβ pathology in plaque‐bearing double‐transgenic amyloid precursor protein (APP)swe /presenilin 1 (PS1)ΔE9 mutants. In addition, we addressed whether serotonin depletion affects Aβ pathology. Treatments were assessed by measurement of serotonin transporter occupancy and high‐performance liquid chromatography. The effect of paroxetine on Aβ pathology was evaluated by stereological plaque load estimation and Aβ42 /Aβ40 ratio by enzyme‐linked immunosorbent assay. Results: Contrary to our hypothesis, paroxetine therapy did not mitigate Aβ pathology, and depletion of brain serotonin did not exacerbate Aβ pathology. However, chronic paroxetine therapy increased mortality in APPswe /PS1ΔE9 transgenic mice. Discussion: Our results question the ability of selective serotonin reuptake inhibitor therapy to ameliorate established Aβ pathology. The severe adverse effect of paroxetine may discourage its use for disease‐modifying purposes in Alzheimer's disease. Highlights: Chronic paroxetine treatment does not mitigate established amyloid‐β pathology in APPswe /PS1ΔE9 mice. Chronic paroxetine treatment increases the mortality of APPswe /PS1ΔE9 but not littermate wild‐type mice. Serotonergic depletion does not influence established amyloid‐β pathology in APPswe /PS1ΔE9 mice.